2006
DOI: 10.1002/pssc.200565146
|View full text |Cite
|
Sign up to set email alerts
|

Extremely smooth surface morphology of GaN‐based layers on misoriented GaN substrates for high‐power blue‐violet lasers

Abstract: We have successfully realized a very smooth surface morphology of GaN-based epitaxial layers on n-GaN (0001) substrates with the misorientation angle of approximately 0.2• only toward [1100] direction, which is confirmed using Nomarski microscopy and atomic force microscopy. In x-ray diffraction spectra, the narrow width of the satellite peak of superlattices also indicated the smooth surface morphology and abrupt interfaces of the epitaxial layers on the GaN (0001) substrate with the misorientation angle only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…LDs [4,5] and high efficiency LEDs [6] fabricated on free-standing GaN substrates have benefit from these advantages. Atomic steps can be straight because of low dislocation density and some groups reported such straight steps on GaN substrates [7,8]. However, undesirable hillocks [9][10][11] and wavy [11][12][13] surface morphologies on homoepitaxial c-plane GaN layers have been observed.…”
Section: Introductionmentioning
confidence: 98%
“…LDs [4,5] and high efficiency LEDs [6] fabricated on free-standing GaN substrates have benefit from these advantages. Atomic steps can be straight because of low dislocation density and some groups reported such straight steps on GaN substrates [7,8]. However, undesirable hillocks [9][10][11] and wavy [11][12][13] surface morphologies on homoepitaxial c-plane GaN layers have been observed.…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, the misoriented substrates are also interesting in terms of epitaxial growth and device characteristics, as previously reported concerning various mate-rial systems such as InGaAlP/GaAs [5], GaN/sapphire [6,7], or GaN/ SiC [8]. In previous work, it was demonstrated that the surface morphology of GaN-based layers was improved when the layers were grown on GaN (0001) substrates with misorientation toward [1100] direction, rather than when the layers were grown on GaN (0001) substrates with misorientation toward [1120] direction, using atomic force microscopy and X-ray diffraction [9]. This difference in the surface morphology on GaN substrates with different misorientation directions was closely related to anisotropic lateral growth rates in [1100] and [1120] directions [10].…”
mentioning
confidence: 99%
“…Additional investigations by Xu et al concerned with the homoepitaxial growth of (a) Si-doped, n-type and Mg-doped, p-type 3 mm thick GaN films on similarly oriented wafers and (b) both undoped and doped films on vicinal GaN(0001) wafers offcut 11, 21, 41 and 81 have also been reported [21]. Subsequent related investigations by Tachibana et al [22] concerned with atomic force microscopy (AFM) and X-ray diffraction of GaN homoepitaxial layers grown on HVPE, n-type GaN(0001) substrates off-cut 0.21 towards [11 00] and [112 0] revealed the formation of a smooth morphology only on the surface of the former layer.…”
Section: Introductionmentioning
confidence: 91%